Beyond the War for Talent Hype: Occupational and Organisational Change in the Business Professions - Morris, T; Pinnington, A (John Benjamin Publishing Company, 2002)
Paradox — the simultaneous existence of two inconsistent states — has become orthodox. The orthodox is now the paradox. The orthodox world of ordering, controlling and organizing is increasingly opposed to a normalizing world of disordering, disrupting and disorganizing. And organization studies cannot avoid changing its conceptions of reality as that reality changes. In the future, organization studies will be the study of paradox, how to understand it, how to use it. In this book of original contributions addressed to management and organization paradoxes the authors address the new state of the field in terms of representations — representing paradoxes — and materialisations — materialising paradoxes. The themes — although varied, ranging from dialectics to internal tensions; from collaborations to ethics and value conflicts; from resistant labourers and wharfies to cartoon characters such as The Simpsons; from the irrationalities of finance to the psychoanalytic rationalities of auditing, and from issues of governance in Asian and international business to the composition of the new knowledge work force in the business professions — cohere around core aspects of paradoxicality. Overall, the contributions to Management and Organization Paradoxes are diverse and challenging. Each contribution takes a different angle on the central theme. All of the chapters illuminate diverse aspects of contemporary paradoxes in management and organization theory. The book provides, in each of its chapters, a challenge to the still overwhelmingly rationalist views of theory and practice that dominate the field and provides new directions for understanding organizations and management.